An Assessment of the Demographic Characteristics of Patients with Benign Prostate Hypertrophy at Federal Medical Centre, Azare from January 2014 to December 2018 - Binni, Muhammad Amina; Idris, Zago Salisu (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This research investigates the demographic characteristics of patients diagnosed with Benign Prostate Hypertrophy (BPH) at the Federal Medical Centre (FMC) Azare, Bauchi State, from 2014 to 2018. BPH, characterized by the non-cancerous enlargement of the prostate gland, is recognized as the most common urological condition affecting adult males globally. The study aims to determine the number of patients diagnosed and treated with BPH, identify the most affected age group, examine the family structure most commonly associated with the condition, and assess the parity of affected patients. A descriptive survey design was adopted, utilizing anecdotal records from 423 patients diagnosed with BPH during the study period representing a full enumeration of the target population. Data were analyzed using percentages and presented in frequency distribution tables. The findings revealed that the highest number of BPH cases occurred in 2018. The most affected age group was between 50 and 80 years (44%), with patients from polygamous families comprising the majority (79%). Furthermore, 54% of patients had five or more children. Based on these results, the study recommends that health professionals intensify educational efforts targeting men at risk of BPH, focusing on its causes and prevention. Additionally, government support is urged, particularly in the provision of medical assistance such as medications for affected individuals.